Hubungan Depresi Terhadap Interaksi Sosial Lansia Di UPTD Griya Werdha Jambangan Surabaya - Elfa Lailatul Izza (2018)
Depression in the elderly ia a form disorder in a pathological feeling characterized by feelings of sadness, low self-esteem, guilt, despair, feelingempty, feeling depressed, suffering, irritability, eatingdisorders, sleeplessness and anxiety. So that will interfere with social interaction, in a mutual relationship that affect each other between individuals, social groups and society. The purpose of this study was to determine the relationship of depression to social interaction of elderly in UPTD Griya Werdha Jambangan Surabaya. This research use cross sectional approach method. The population in this study is elderly living in UPTD Griya Werdha Jambangan Surabaya 30 respondents, with purposive sampling. Sampling technique data measurement tools are questionnaires. Statistical analysis using chi square test. Result of significance value 0,05. The social interaction status found that most respondents were medium category 15 respondents (50,0%), always 13 respondents (43,3%) and never 2 respondents (6,7%). Moderately depressed elderly were 15 respondents (50,0%), no depression 4 respondents (13,3%), mild depression 6 respondents (20,0%) and major depression 5 respondents (16,7%). Statistical calculation shows there is relationship between depression with social interaction P value <0,05 that is 0,001 <0,05, so HO rejected mean there is relation between depression with social interaction of elderly in UPTD Griya Werdha Jambangan Surabaya. Conclusions in the elderly further enhance social interaction with fellow elderly living in the enviroment around the orphanage, as well as related parties in reducing the occurrence of depression, by playing an active role in activities held by institutions, health offces, social services and students.